Geology Of The Rome Zeolite Deposit, Malheur County, Oregon - Introduction - K. N. Santini (Society for Mining, Metallurgy & Exploration, 1982)
Natural zeolites are gaining recognition as an important commodity with an increasing number of industrial and consumer applications. This potential has prompted the Anaconda Minerals Company and other firms to investigate occurrences and markets for zeolites. The deposits of mordenite-rich tuff at Rome are of interest for their economic potential and for the excellent opportunity they provide to study a zeolite deposit formed in a hydrologically closed basin. Location The Rome property is located approximately 9 km west of Rome, Oregon, in Townships 31S. and 32S., Range 41E., Malheur County. It lies within the Owyhee Uplands of the northern Basin and Range physiographic province (Figure 1). The area discussed here includes a major portion of the depositional basin in which the zeolitic tuffs occur.